Boron nitride powder, inorganic filler, and method for producing boron nitride powder
Patent Information
- Application Number
- JP2025058101
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2026-10-14
- Estimated Expiration
- 2045-03-31
AI Technical Summary
【0012】 本開示によれば、熱伝導率に優れ、かつ、絶縁性に優れる樹脂成形体を提供可能な窒化ホウ素粉末を提供できる。
Smart Images

Figure 2026165625000002 
Figure 2026165625000003 
Figure 2026165625000001
Abstract
Description
[Technical Field]
[0001] This disclosure relates to boron nitride powder, inorganic fillers, and methods for producing boron nitride powder. [Background technology]
[0002] Boron nitride powder possesses high thermal conductivity and insulating properties, and is widely used in applications such as thermal conductive fillers and insulating fillers. In particular, boron nitride powder is used as a filler in heat dissipation components where high thermal conductivity is required.
[0003] The primary particles of hexagonal boron nitride have a relatively thin, flaky shape, and when filled into resins and molded, the primary particles tend to orient in a certain direction due to molding pressure and other factors. For example, in a resin sheet formed by extrusion molding after filling with hexagonal boron nitride powder, the primary particles of boron nitride generally tend to orient so that the main surface of the resin sheet and the long axis of the primary particles are parallel. Furthermore, due to the anisotropy of their shape, the primary particles of hexagonal boron nitride can exhibit anisotropy in various physical properties. While the thermal conductivity of the primary particles of hexagonal boron nitride in the in-plane direction (a-axis direction) is high at around 400 W / (m·K), the thermal conductivity in the thickness direction (c-axis direction) remains at around 2 W / (m·K), demonstrating significant anisotropy in physical properties depending on the direction.
[0004] For the reasons mentioned above, methods are being considered to take advantage of the high thermal conductivity of hexagonal boron nitride in the a-axis direction when preparing a heat dissipation sheet using hexagonal boron nitride powder as a filler in resin, by adjusting the orientation so that the a-axis direction of the primary particles is parallel to the thickness direction of the heat dissipation sheet. For example, a technique is known for orienting the hexagonal boron nitride primary particles so that the a-axis direction is parallel to the thickness direction of the heat dissipation sheet (e.g., Patent Document 1). [Prior art documents] [Patent Documents]
[0005] [Patent Document 1] Japanese Patent Publication No. 2000-154265 [Overview of the Initiative] [Problems that the invention aims to solve]
[0006] Resin molded articles containing boron nitride powder (for example, heat dissipation sheets) are used as heat-generating components in electronic devices, for example, and therefore require not only excellent thermal conductivity but also excellent insulation properties.
[0007] The purpose of this disclosure is to provide a boron nitride powder capable of providing a resin molded article with excellent thermal conductivity and excellent insulating properties. [Means for solving the problem]
[0008] To improve the insulating properties of resin molded articles, it is desirable to reduce the fine voids generated in the resin molded article during the manufacturing process. From the viewpoint of reducing voids, surface modification such as adjusting the specific surface area of the boron nitride particles filled into the resin can be considered. However, it is not easy to estimate the proportion of voids when the resin molded article is prepared before filling it into the resin, and no appropriate evaluation index has been provided. Through our research, the inventors have found that by preparing a molded article made of boron nitride powder by compression molding at a predetermined pressure, and performing measurements on such a compressed molded article using the mercury intrusion method, the proportion of pores in a compressed molded article with a predetermined integrated pore volume in the pore distribution curve is useful as an index for estimating the proportion of voids when the resin molded article is prepared. The information obtained by the mercury intrusion method on the compressed molded article as described above differs from the information obtained by the mercury intrusion method on boron nitride powder that is not compressed. This disclosure is based on the above findings.
[0009] This section further explains the differences between the pore distribution curve obtained by the mercury intrusion method for boron nitride powder and the pore distribution curve obtained by the mercury intrusion method for a compression molded body of boron nitride powder. When a resin molded body is obtained by molding a mixture of boron nitride powder and resin, some of the aggregated particles constituting the boron nitride powder may collapse and deform due to the molding pressure. Therefore, unlike the pore distribution curve of the powder, the pore distribution curve of the compression molded body can reflect the collapse and deformation of some of the aggregated particles, allowing for a more precise evaluation of the voids in the resin molded body. Furthermore, since the particle size and particle strength of the powder are not uniform, for example, if particles with a large pore size have high particle strength, even if there are few voids in the powder state, large voids may remain when the powder is compressed into a molded body. Thus, the amount of voids in the powder does not necessarily correspond to the amount of voids in the compression molded body. Based on the above, by using the pore distribution curve obtained by the mercury intrusion method for compression molded bodies, the proportion of voids in resin molded bodies containing boron nitride powder can be evaluated more precisely.
[0010] This disclosure provides the following [1] to [6].
[0011] [1] Boron nitride powder, The boron nitride powder includes aggregated particles composed of aggregated primary particles of hexagonal boron nitride, The crushing strength of the aggregated particles is 10 MPa or more. The orientation index of the boron nitride powder is 10 or less. A molded body made of the boron nitride powder is prepared by compressing the boron nitride powder at a pressure of 20 MPa, and in the pore distribution curve of the molded body obtained by measurement using the mercury intrusion method, When the cumulative pore volume in the range of pore diameters from 0.001 to 300 μm is denoted as the cumulative pore volume X, and the cumulative pore volume in the range of pore diameters from 1 to 300 μm is denoted as the cumulative pore volume Y, the ratio of the cumulative pore volume Y to the cumulative pore volume X is 30% or less. Boron nitride powder in which the highest peak of pore volume is located in the range of pore diameter 1 μm or less. [2] The boron nitride powder according to [1], wherein the cumulative pore volume X is 0.5 mL / g or less. [3] The boron nitride powder according to [1] or [2], having an average particle diameter of 10 to 100 μm. [4] A bulk density of 0.7 g / cm 3 or more, the boron nitride powder according to any one of [1] to [3]. [5] The boron nitride powder according to any one of [1] to [4], and at least one aluminum compound selected from the group consisting of aluminum oxide and aluminum nitride, an inorganic filler comprising the same. [6] A nitriding step of firing boron carbide powder in a nitrogen pressurized atmosphere to obtain boron carbonitride powder, a firing step of firing the boron carbonitride powder in the atmosphere, and a decarburization step of firing the boron carbonitride powder that has undergone the firing step in an atmosphere containing nitrogen to obtain boron nitride powder, the method comprising: The method for producing boron nitride powder, wherein in the decarburization step, diboron trioxide gas is supplied to the boron carbonitride powder. Effects of the Invention
[0012] According to the present disclosure, it is possible to provide a boron nitride powder that can provide a resin molded article having excellent thermal conductivity and excellent insulating properties. Brief Description of the Drawings
[0013] [Figure 1] Figure 1 is a scanning electron micrograph showing the boron nitride powder according to Example 1. [Figure 2] Figure 2 is a scanning electron micrograph showing the boron nitride powder according to Comparative Example 1. Modes for Carrying Out the Invention
[0014] Embodiments of the present disclosure are described below. However, the following embodiments are illustrative for the purpose of illustrating the present disclosure and are not intended to limit the present disclosure to the following. In this specification, numerical ranges indicated by the symbol "~" include lower and upper limits. That is, numerical ranges indicated by "x~y" mean x or greater and y or less. Also, in this specification, "pore diameter" means the diameter of a pore.
[0015] Unless otherwise specified, the materials exemplified herein may be used individually or in combination of two or more. The content of each component in a composition means the total amount of any multiple substances present in the composition, unless otherwise specified, if there are multiple substances corresponding to each component in the composition.
[0016] One embodiment of the present disclosure is a boron nitride powder comprising aggregated particles composed of aggregated primary particles of hexagonal boron nitride, wherein the crushing strength of the aggregated particles is 10 MPa or more, and the orientation index of the boron nitride powder is 10 or less. The boron nitride powder is obtained by preparing a molded body made of the boron nitride powder by compressing the boron nitride powder at a pressure of 20 MPa, and in the pore distribution curve of the molded body obtained by measurement by the mercury intrusion method for the molded body, when the integrated pore volume in the range of pore diameters from 0.001 to 300 μm is defined as integrated pore volume X, and the integrated pore volume in the range of pore diameters from 1 to 300 μm is defined as integrated pore volume Y, the ratio of integrated pore volume Y to integrated pore volume X (hereinafter also simply referred to as "ratio of integrated pore volume Y") is 30% or less, and the highest peak of pore volume exists in the range of pore diameters of 1 μm or less.
[0017] The boron nitride described above exhibits excellent thermal conductivity and insulation properties. The following factors are presumed to be the reason for this, although the factors are not limited to those listed below. The boron nitride powder contains aggregated particles composed of aggregated primary particles of hexagonal boron nitride, and its orientation index is 10 or less. The proportion of aggregated particles, in which the primary particles (single particles) of hexagonal boron nitride in the powder are substantially unoriented, is relatively high. Furthermore, the crush strength of the aggregated particles contained in the boron nitride powder is 10 MPa or more, making particle breakage very unlikely during the pressing process. In addition, since primary particles do not grow inside the aggregated particles, the orientation does not increase even if the aggregated particles are broken. As a result, the boron nitride powder conducts heat isotropically, and the resin molded articles produced from it exhibit excellent thermal conductivity. Furthermore, when a molded body made of boron nitride powder is prepared by compressing the boron nitride powder according to this embodiment at a predetermined pressure, the pore distribution curve of the molded body obtained by measurement using the mercury intrusion method shows that the proportion of the integrated pore volume Y is 30% or less, and the highest peak of pore volume exists in the range where the pore diameter is 1 μm or less. This boron nitride powder has high crush strength and contains aggregated particles that do not completely collapse even under molding pressure, meaning that pores formed inside the aggregated particles can remain, while the proportion of regions with large pore diameters (e.g., voids formed between aggregated particles) is low, and furthermore, the highest peak belongs to the region with small pore diameters, which means that the voids inside the aggregated particles are also small. Therefore, when such boron nitride powder is used in a resin molded body, voids can be reduced even in the resin molded body. As a result, dielectric breakdown of the resin molded body due to voids can be suppressed, and the insulating properties of the resin molded body can be improved. Furthermore, the small number of voids suggests that the primary particles within the aggregated particles, or the aggregated particles themselves, are in close contact, and from this perspective as well, the boron nitride powder exhibits excellent thermal conductivity.
[0018] As described above, the boron nitride powder according to this embodiment has small internal voids and high density in its aggregated particles, which allows for an improvement in the amount of boron nitride powder that can be packed into a resin when mixed in the same volume as conventional boron nitride powder. In other words, the viscosity of the resin composition obtained when boron nitride powder is mixed into a resin to the same amount as conventionally can be easily reduced. By increasing the amount of boron nitride powder mixed into the resin composition, it is easier to obtain a resin molded article with superior thermal conductivity. When using conventional boron nitride powder and attempting to increase the amount mixed into a resin composition, there are concerns that the viscosity will increase, reducing handling ease, or that the insulation will decrease due to an increase in the generation of voids. However, in the case of the boron nitride powder according to this disclosure, as described above, the decrease in insulation can also be suppressed.
[0019] Furthermore, as can be seen from Figure 1 (a scanning electron microscope image showing the boron nitride powder according to Example 1 described later), the boron nitride powder according to this embodiment extremely suppresses the growth of primary boron nitride particles, resulting in virtually no collapse of clumpy particles due to primary particle growth, and a significantly reduced amount of flaky primary boron nitride particles. In addition, primary particles do not grow on the surface of the agglomerated boron nitride particles, and interference between primary particles between agglomerated particles is very unlikely, resulting in excellent packing properties. As a result, the viscosity of the resin composition can be easily reduced using the boron nitride powder according to this embodiment.
[0020] In this specification, an aggregated particle refers to a secondary particle that exists in a state where five or more primary particles (single particles) are aggregated, and the c-axis direction of each primary particle is random. The aggregated state of primary particles can be confirmed, for example, by SEM (scanning electron microscope).
[0021] The boron nitride powder described above may include primary particles of hexagonal boron nitride and aggregated particles composed of multiple aggregated primary particles of hexagonal boron nitride.
[0022] The orientation index of the boron nitride powder according to this embodiment may be 2 or more, 4 or more, or 6 or more. From the viewpoint of further improving the thermal conductivity of the resin molded article, the orientation index of the boron nitride powder may be 9 or less, 8.5 or less, 8 or less, 7.7 or less, or 7.3 or less. The orientation index of the boron nitride powder may be adjusted within the above range, for example, 2 to 10.
[0023] In this specification, the orientation index refers to a value measured according to the following method: An X-ray diffraction spectrum of boron nitride powder is obtained by performing an X-ray diffraction measurement on the boron nitride powder, and peak intensities I(002) and I(100) corresponding to the (002) plane and (100) plane are obtained from the said X-ray diffraction spectrum. The orientation index [I(002) / I(100)] of the boron nitride powder is calculated using the obtained peak intensities. As an X-ray diffractometer, for example, "ULTIMA-IV" (product name) manufactured by Rigaku Corporation can be used.
[0024] Since the orientation index is measured on boron nitride powder, if aggregated particles are present in the powder and their proportion is large, the orientation index value tends to decrease and approach a value of around 6 to 7. On the other hand, if the powder consists only of primary particles without aggregated particles, or if the proportion of the above primary particles is large, the orientation index value tends to increase.
[0025] The crushing strength of the aggregated particles in boron nitride powder is 10 MPa or higher. A crushing strength of 10 MPa or higher suppresses the collapse of the aggregated particles even when the resin molded body is subjected to high pressure. Furthermore, as can be understood from the mercury intrusion method described above, the internal voids of the aggregated particles are small. This improves the thermal conductivity and insulation properties of the resin molded body. From the viewpoint of further improving the thermal conductivity of the resin molded body, the crushing strength of the aggregated particles in boron nitride powder may be 11 MPa or higher, 12 MPa or higher, 15 MPa or higher, 20 MPa or higher, or 25 MPa or higher. From the viewpoint of reducing the voids in the resin molded body and further improving the insulation properties of the resin molded body, the crushing strength of the aggregated particles in boron nitride powder may be 50 MPa or lower, 45 MPa or lower, 40 MPa or lower, 35 MPa or lower, or 15 MPa or lower. The crushing strength of the aggregated particles may be adjusted within the above range, for example, 10 to 50 MPa or 15 to 35 MPa.
[0026] In this specification, crush strength refers to the value measured in accordance with JIS R 1639-5:2007 "Fine ceramics - Method for measuring granular properties - Part 5: Single granular crush strength". The crush strength σ (unit: MPa) of a single granule is calculated using the formula σ = α × P / (π × d²) from the values of the dimensionless number α (α = 2.48), which changes depending on the position within the granule, the crush test force P (unit: N), and the particle diameter d (unit: μm). The measurement shall be performed on 20 or more granules, and the value at the point of cumulative fracture rate of 63.2% shall be calculated. A micro-compression tester can be used for the measurement. For example, the "MCT-210" (product name) manufactured by Shimadzu Corporation can be used as a micro-compression tester.
[0027] The average particle diameter (D50) of boron nitride may be 10 μm or more, 20 μm or more, or 25 μm or more from the viewpoint of easily ensuring the thermal conductivity of the resin molded body. The average particle diameter of boron nitride may be 100 μm or less, 80 μm or less, 60 μm or less, 50 μm or less, 39 μm or less, or 35 μm or less from the viewpoints of further improving the insulation properties of the resin molded body and reducing the viscosity of the resin composition. The average particle diameter of the above boron nitride powder may be adjusted within the above-mentioned range, and may be, for example, 10 to 100 μm.
[0028] The average particle diameter (D50) in the present specification means a value measured in accordance with the method described in JIS Z 8825:2013 "Particle size analysis - Laser diffraction and scattering method". A laser diffraction scattering particle size distribution analyzer is used for the measurement. As the laser diffraction scattering particle size distribution analyzer, for example, "LS-13 320" (trade name) manufactured by Beckman Coulter, Inc., and Microtrac "MT-3300EXII" (trade name) manufactured by MicrotracBEL Corp., etc. can be used. In addition, when measuring the average particle diameter of the boron nitride powder, the measurement shall be performed without subjecting the powder to be measured to treatment with a homogenizer or the like.
[0029] The bulk density of the boron nitride powder may be 0.7 g / cm 3 or more, 0.72 g / cm 3 or more, 0.75 g / cm 3 or more, 0.77 g / cm 3 or more, or 0.81 g / cm 3 or more. The bulk density of the boron nitride powder may be 2 g / cm 3 or less, 1.5 g / cm 3 or less, or 1 g / cm 3 or less. The bulk density of the boron nitride powder may be adjusted within the above-mentioned range, and may be, for example, 0.7 to 2 g / cm 3 or 0.72 to 1.5 g / cm 3 .
[0030] In this specification, bulk density refers to the value obtained in accordance with the method described in JIS R 1628:1997 "Method for Measuring the Bulk Density of Fine Ceramic Powders". Commercially available equipment can be used for measurement.
[0031] In this embodiment, the boron nitride powder is molded into a molded body by compression molding at a pressure of 20 MPa. The ratio of the integrated pore volume Y to the integrated pore volume X in the pore distribution curve of the molded body, obtained by measurement using the mercury intrusion method, is a predetermined ratio, and the maximum peak position in the pore distribution curve is in the region of small pores. The pore distribution in this specification is measured in accordance with the description in JIS R 1655:2003 "Method for testing pore size distribution of molded bodies of fine ceramics by mercury intrusion method". The range of pore diameter in the pore distribution curve may be 0.001 to 300 μm. Measurement by mercury intrusion may be performed using a mercury porosimeter. The pore distribution curve of the molded body exhibits different behavior from the pore distribution curve of powdered boron nitride powder.
[0032] In this embodiment, the boron nitride powder has a ratio of 30% or less of the integrated pore volume Y to the integrated pore volume X in the pore distribution curve of the molded body. A ratio of 30% or less of integrated pore volume Y in the pore distribution curve of the molded body indicates that the proportion of pores with relatively large diameters is small compared to the whole. In other words, it indicates that the molded body is denser. Boron nitride powder capable of preparing such a molded body can be filled into resin, kneaded, molded, etc., and achieve a denser arrangement within the resin. As a result, the boron nitride powder densely fills the resin molded body, reducing voids in the resin molded body and suppressing dielectric breakdown caused by voids, thereby improving the insulation properties of the resin molded body. Furthermore, the thermal conductivity of the resin molded body is also improved by the close contact between primary particles within the aggregated particles or between aggregated particles themselves. The ratio of the cumulative pore volume Y can be adjusted, for example, in the decarburization process described later, by controlling the content of the boron source relative to the total mass of raw material 1, the amount of diboron trioxide gas supplied, and the particle size of aggregated particles.
[0033] In the pore distribution curve of the above molded body, the ratio of the integrated pore volume Y may be 1% or more, 3% or more, 5% or more, 10% or more, 13% or more, or 14.5% or more, from the viewpoint of further improving the thermal conductivity of the resin molded body. In the pore distribution curve of the above molded body, the ratio of the integrated pore volume Y may be 25% or less, 22% or less, 20% or less, 17% or less, 14.5% or less, 12% or less, or 10% or less, from the viewpoint of further improving the insulating properties of the resin molded body. In the pore distribution curve of the above molded body, the ratio of the integrated pore volume Y may be adjusted within the above range, for example, 1 to 30% or 3 to 25%.
[0034] In the pore distribution curve of the above-mentioned molded body, the highest peak in pore volume exists in the range of pore diameters of 1 μm or less. "The existence of a peak in the range of 1 μm or less" means that there exists a pore diameter (pore diameter where the slope of the pore distribution curve changes from positive to negative) in the range of 1 μm or less where the pore volume is maximized. The fact that the highest peak in the pore distribution curve of the above-mentioned molded body exists in the range of pore diameters of 1 μm or less means that the molded body of boron nitride powder is densely packed, and that the voids inside the aggregated particles, whose shape is maintained, are also fine. Furthermore, the boron nitride powder densely packs the resin molded body, reducing the voids in the resin molded body and suppressing dielectric breakdown caused by voids, thereby improving the insulation properties of the resin molded body. In addition, the close contact between primary particles within the aggregated particles or between aggregated particles themselves improves the thermal conductivity of the resin molded body. The location of the highest peak in pore volume can be adjusted, for example, in the decarburization process described later, by controlling the boron source content relative to the total mass of raw material 1, the supply amount of diboron trioxide gas, and the particle size of aggregated particles.
[0035] In the pore distribution curve of the above molded body, the range in which the highest peak of pore volume exists may be 0.1 μm or more, 0.2 μm or more, 0.3 μm or more, or 0.5 μm or more. In the pore distribution curve of the above molded body, the range in which the highest peak of pore volume exists may be 0.95 μm or less, 0.9 μm or less, or 0.85 μm or less, from the viewpoint of further improving the insulating properties of the resin molded body. In the pore distribution curve of the above molded body, the range in which the highest peak of pore volume exists may be adjusted within the above range, for example, 0.1 to 0.95 μm or 0.2 to 0.9 μm.
[0036] In the pore distribution curve of the molded body described above, the number of pore volume peaks may be 1 or 2 or more, and may be 5 or less.
[0037] In the pore distribution curve of the molded body described above, the integrated pore volume X may be 0.1 mL / g or more, 0.15 mL / g or more, 0.2 mL / g or more, 0.3 mL / g or more, 0.34 mL / g or more, 0.36 mL / g or more, or 0.4 mL / g or more, from the viewpoint of further improving the thermal conductivity of the resin molded body. In the pore distribution curve of the molded body described above, the integrated pore volume X may be 0.5 mL / g or less, 0.45 mL / g or less, or 0.4 mL / g or less, from the viewpoint of further improving the insulating properties of the resin molded body. In the pore distribution curve of the molded body described above, the integrated pore volume X may be adjusted within the above range, for example, 0.1 to 0.5 mL / g, 0.15 to 0.45 mL / g, or 0.2 to 0.4 mL / g. The cumulative pore volume X can be adjusted, for example, in the decarburization process described later, by controlling the content of the boron source relative to the total mass of raw material 1, the supply amount of diboron trioxide gas, and the particle size of aggregated particles.
[0038] One embodiment of this disclosure is a method for evaluating boron nitride powder, comprising: a measurement step of preparing a molded body made of boron nitride powder by compression molding boron nitride powder at a pressure greater than 13 MPa and less than or equal to 50 MPa; a measurement step of obtaining a pore distribution curve of the molded body by measurement using a mercury intrusion method; and an evaluation step of evaluating the pore distribution of the molded body from the pore distribution curve. The inventors have found that by evaluating the pore distribution of a molded body obtained by compression molding boron nitride powder from the pore distribution curve of the molded body, the insulating properties of a resin molded body can be predicted without manufacturing a resin molded body. In other words, one aspect of this disclosure can be said to be providing a method for evaluating boron nitride powder that evaluates the insulating properties of a resin molded body from a compression molded body of boron nitride powder.
[0039] In the pore distribution measurement process, the molding pressure of the molded body may be 14 MPa or higher, 15 MPa or higher, or 16 MPa or higher, and may be 30 MPa or lower or 25 MPa or lower.
[0040] In the evaluation process, the evaluation of pore distribution includes the percentage of the cumulative pore volume Y, the highest peak position of the pore volume, and the cumulative pore volume X.
[0041] The orientation index of the boron nitride powder to be evaluated in the above evaluation method may be the same as the orientation index of the boron nitride powder described above.
[0042] In the evaluation method described above, the crushing strength of the boron nitride aggregated particles to be evaluated may be the same as that of the aggregated particles described above.
[0043] In the evaluation method described above, the average particle size of the boron nitride powder to be evaluated may be the same as the average particle size of the boron nitride powder described above.
[0044] In the evaluation method described above, the bulk density of the boron nitride powder to be evaluated may be the same as the bulk density of the boron nitride powder described above.
[0045] One embodiment of the present disclosure is a method for selecting boron nitride powder suitable for inorganic fillers, comprising: measuring the crushing strength of aggregated particles composed of aggregated primary particles of hexagonal boron nitride; measuring the orientation index of the boron nitride powder containing the aggregated particles; preparing a molded body made of boron nitride powder by compressing the boron nitride powder at a pressure of 20 MPa, and obtaining a pore distribution curve of the molded body by measurement using the mercury intrusion method; and selecting boron nitride powder in which the crushing strength of the aggregated particles is 10 MPa or more, the orientation index of the boron nitride powder is 10 or less, and in the pore distribution curve of the molded body, the ratio of the integrated pore volume Y is 30% or less, and the highest peak of pore volume is located in the range of pore diameter 1 μm or less. In the selection step, the order in which the selection conditions are applied is not particularly limited. The boron nitride powder selected as described above is suitable as a heat dissipation filler for preparing resin molded articles that have excellent thermal conductivity and excellent insulating properties.
[0046] As a selection criterion, the orientation index may be 2 or higher, 4 or higher, or 6 or higher. As a selection criterion, the orientation index may be 9 or lower, 8.5 or lower, 8 or lower, 7.7 or lower, or 7.3 or lower, from the viewpoint of further improving the thermal conductivity of the resin molded article. As a selection criterion, the orientation index may be adjusted within the above range, for example, 2 to 10.
[0047] As a sorting condition, the crushing strength of the aggregated particles may be 11 MPa or higher, 12 MPa or higher, 15 MPa or higher, 20 MPa or higher, or 25 MPa or higher, from the viewpoint of further improving the thermal conductivity and insulation properties of the resin molded body. As a sorting condition, the crushing strength of the aggregated particles may be 50 MPa or lower, 45 MPa or lower, 40 MPa or lower, 35 MPa or lower, or 15 MPa or lower, from the viewpoint of reducing the voids in the resin molded body and further improving the insulation properties of the resin molded body. As a sorting condition, the crushing strength of the aggregated particles may be adjusted within the above range, for example, 10 to 50 MPa or 15 to 35 MPa.
[0048] The above sorting method may further include a step of measuring the average particle size of the boron nitride powder. As sorting conditions, the average particle size may be 10 μm or more, 20 μm or more, or 25 μm or more, from the viewpoint of ensuring the thermal conductivity of the resin molded article. As sorting conditions, the average particle size may be 100 μm or less, 80 μm or less, 60 μm or less, 50 μm or less, 39 μm or less, or 35 μm or less, from the viewpoint of further improving the insulating properties of the resin molded article and reducing the viscosity of the resin composition. As sorting conditions, the average particle size may be adjusted within the above range, for example, 10 to 100 μm.
[0049] The above sorting method may further include a step of measuring the bulk density of the boron nitride powder. As a sorting condition, the bulk density is set to 0.7 g / cm³ from the viewpoint of further improving the insulating properties of the resin molded article and reducing the viscosity of the resin composition. 3 More than 0.72g / cm 3 More than 0.75g / cm 3 More than 0.77g / cm 3 or more, or 0.81 g / cm³ 3 The above is sufficient. As a sorting criterion, the bulk density should be 2 g / cm³. 3 Below 1.5g / cm 3 The following or 1 g / cm³ 3 The following conditions may apply. As a sorting condition, the bulk density may be adjusted within the above range, for example, 0.7 to 2 g / cm³. 3 Or 0.72~1.5 g / cm³ 3 That's fine.
[0050] As a selection criterion, the percentage of the cumulative pore volume Y may be 1% or more, 3% or more, 5% or more, 10% or more, 13% or more, or 14.5% or more, from the viewpoint of further improving the thermal conductivity of the resin molded body. As a selection criterion, the percentage of the cumulative pore volume Y may be 25% or less, 22% or less, 20% or less, 17% or less, 14.5% or less, 12% or less, or 10% or less, from the viewpoint of further improving the insulating properties of the resin molded body. As a selection criterion, the percentage of the cumulative pore volume Y may be adjusted within the above range, for example, 1 to 30% or 3 to 25%.
[0051] As a selection criterion, the range in which the highest peak of pore volume exists may be 0.1 μm or more, 0.2 μm or more, 0.3 μm or more, or 0.5 μm or more. As a selection criterion, the range in which the highest peak of pore volume exists may be 0.95 μm or less, 0.9 μm or less, or 0.85 μm or less, from the viewpoint of further improving the insulating properties of the resin molded article. As a selection criterion, the range in which the highest peak of pore volume exists may be adjusted within the above range, for example, 0.1 to 0.95 μm or 0.2 to 0.9 μm.
[0052] In the above sorting method, boron nitride powder may be further sorted based on the integrated pore volume X in the pore distribution curve of the molded body. As sorting conditions, the integrated pore volume X may be 0.1 mL / g or more, 0.15 mL / g or more, 0.2 mL / g or more, 0.3 mL / g or more, 0.34 mL / g or more, 0.36 mL / g or more, or 0.4 mL / g or more, from the viewpoint of further improving the thermal conductivity of the resin molded body. As sorting conditions, the integrated pore volume X may be 0.5 mL / g or less, 0.45 mL / g or less, or 0.4 mL / g or less, from the viewpoint of further improving the insulating properties of the resin molded body. As sorting conditions, the integrated pore volume X may be adjusted within the above range, for example, 0.1 to 0.5 mL / g, 0.15 to 0.45 mL / g, or 0.2 to 0.4 mL / g.
[0053] One embodiment of a method for producing boron nitride powder comprises a nitriding step of obtaining boron carbonitride powder by calcining boron carbide powder under a nitrogen-pressurized atmosphere; a calcination step of calcining the boron carbonitride powder under an atmosphere; and a decarburization step of obtaining boron nitride powder by calcining the boron carbonitride powder that has undergone the calcination step under a nitrogen-containing atmosphere. In the decarburization step, diboron trioxide gas is supplied to the boron carbonitride powder.
[0054] Boron carbide powder may be obtained by calcining a mixture of a boron source and carbon black under an argon atmosphere. The boron source may contain at least one selected from the group consisting of boric acid and boron oxide.
[0055] The boron source content may be 60% by mass or more, 85% by mass or less, or 60-85% by mass, based on the total mass of the boron source and carbon black. The boric acid content, based on the total mass of boric acid and carbon black, may also be within the above-mentioned ranges.
[0056] The calcination temperature when obtaining boron carbide powder may be 1800°C or higher, 2500°C or lower, or 1800 to 2500°C. The calcination time when obtaining boron carbide powder may be 2 hours or more, 8 hours or less, or 2 to 8 hours.
[0057] The average particle size of the boron carbide powder may be 5 μm or larger, 40 μm or smaller, or between 5 and 40 μm. The average particle size of the boron carbide powder is measured in accordance with the method described in JIS Z 8825:2013 "Particle size analysis - Laser diffraction and scattering method".
[0058] The pressure in the nitriding process may be 0.4 MPa or higher or 0.6 MPa or higher, from the viewpoint of allowing the nitriding of boron carbide to proceed more sufficiently. The pressure in the nitriding process may be 1.2 MPa or lower or 1 MPa or lower, from the viewpoint of suppressing an increase in the manufacturing cost of boron nitride powder. The pressure in the nitriding process may be adjusted within the above range, for example, 0.4 to 1.2 MPa or 0.6 to 1 MPa.
[0059] The firing temperature in the nitriding process may be 1500°C or higher or 1800°C or higher, from the viewpoint of allowing the nitriding of boron carbide to proceed more sufficiently. The firing temperature in the nitriding process may be 2500°C or lower or 2300°C or lower, from the viewpoint of suppressing an increase in the manufacturing cost of boron nitride powder. The firing temperature in the nitriding process may be adjusted within the above range, for example, 1500 to 2500°C or 1800 to 2300°C.
[0060] The firing time in the nitriding process may be 10 hours or more, or 20 hours or more, from the viewpoint of allowing the nitriding of boron carbide to proceed more sufficiently. The firing time in the nitriding process may be 50 hours or less, or 40 hours or less, from the viewpoint of suppressing an increase in the manufacturing cost of boron nitride powder. The firing time in the nitriding process may be adjusted within the above range, for example, 10 to 50 hours or 20 to 40 hours.
[0061] In the firing process, the carbon content in the boron carbonitride powder can be reduced by firing the boron carbonitride powder under atmospheric pressure.
[0062] The firing temperature in the firing process may be 400°C or higher or 600°C or higher, from the viewpoint of further reducing the carbon content in the boron carbonitride powder. The firing temperature in the firing process may be 1500°C or lower or 1000°C or lower, from the viewpoint of suppressing the oxidation of boron carbonitride after firing. The firing temperature in the firing process may be adjusted within the above range, for example, 400 to 1500°C or 600 to 1000°C.
[0063] The firing time in the firing process may be 2 hours or more or 4 hours or more, from the viewpoint of further reducing the carbon content in the boron carbonitride powder. The firing time in the firing process may be 15 hours or less or 10 hours or less, from the viewpoint of more sufficiently suppressing a decrease in the processing efficiency of the firing process. The firing time in the firing process may be adjusted within the above range, for example, 2 to 15 hours or 4 to 10 hours.
[0064] After the calcination process and before the decarburization process, the boron carbonitride powder and the boron source may be mixed. The boron source may contain at least one selected from the group consisting of boric acid and boron oxide. From the viewpoint of further improving the crystallinity of boron nitride, the content of the boron source may be 1% by mass or more, or 3% by mass or more, based on the total mass of the boron carbonitride powder and the boron source. From the viewpoint of suppressing the excessive growth of primary particles and producing boron nitride containing bulk particles with superior crushing strength, the content of the boron source may be 30% by mass or less, 20% by mass or less, or 15% by mass or less, based on the total mass of the boron carbonitride powder and the boron source. The content of the boron source may be adjusted within the above range, for example, 1 to 30% by mass or 3 to 20% by mass, based on the total mass of the boron carbonitride powder and the boron source.
[0065] In the decarburization process, diboron trioxide gas is supplied to the boron carbonitride powder. The diboron trioxide gas may be supplied directly, or a solid or liquid boron source may be prepared and the boron source may be volatilized during the decarburization process. The boron source used to supply diboron trioxide gas may include at least one selected from the group consisting of boric acid and boron oxide.
[0066] In the decarburization process, supplying diboron trioxide gas to the boron carbonitride powder allows for the inclusion of undeveloped primary boron nitride particles within the aggregated particles, thereby reducing pores within the aggregated particles. This is presumed to enable the production of boron nitride aggregated particles with high strength and excellent thermal conductivity. Furthermore, because the primary particles present on the surface of the aggregated particles are also undeveloped, the voids between the aggregated particles can be reduced, which is presumed to reduce voids in the resin molded body when used in such a product.
[0067] When preparing a solid or liquid boron source, a raw material 1 containing boron carbonitride powder and a raw material 2 containing a boron source may be prepared, and a decarburization process may be carried out. Specifically, raw material 1 containing boron carbonitride powder is placed in a first container, raw material 2 containing a boron source is placed in a second container, and the first and second containers are placed in the same furnace to supply diboron trioxide gas to the boron carbonitride powder. Raw material 1 may further contain a boron source.
[0068] The amount of raw material 2 may be 50 parts by mass or more, 70 parts by mass or more, 300 parts by mass or less, 200 parts by mass or less, 50 to 300 parts by mass or 70 to 200 parts by mass, per 100 parts by mass of raw material 1.
[0069] The pressure in the decarburization process may be 5 kPa or more and 20 kPa or less, for example, 5 to 20 kPa.
[0070] The firing temperature in the decarburization process may be 1900°C or higher or 1950°C or higher, from the viewpoint of further reducing the carbon content in the boron carbonitride powder. The firing temperature in the decarburization process may be 2500°C or lower or 2200°C or lower, from the viewpoint of suppressing the yellowing of the boron nitride powder. The firing temperature in the decarburization process may be adjusted within the above range, for example, 1900 to 2500°C or 1950 to 2200°C.
[0071] The firing time in the decarburization process may be 1 hour or more or 2 hours or more, from the viewpoint of further reducing the carbon content in the boron carbonitride powder. The firing time in the decarburization process may be 10 hours or less or 7 hours or less, from the viewpoint of more sufficiently suppressing a decrease in the processing efficiency of the decarburization process. The firing time in the decarburization process may be adjusted within the above range, for example, 1 to 10 hours or 2 to 7 hours.
[0072] The boron nitride powder obtained in the decarburization process may contain primary particles of hexagonal boron nitride, may contain aggregated particles composed of multiple aggregated primary particles, or may contain both primary particles and aggregated particles.
[0073] The method for producing boron nitride powder may further include a crushing step after the decarburization step. In the crushing step, the boron nitride powder obtained by crushing may be classified.
[0074] The crushing time in the crushing process may be 5 minutes or more, or 8 minutes or more, and may be 15 minutes or less, or 12 minutes or less, for example, 5 to 15 minutes or 8 to 12 minutes.
[0075] One embodiment of the present disclosure is an inorganic filler comprising the boron nitride powder described above and at least one aluminum compound selected from the group consisting of aluminum oxide and aluminum nitride.
[0076] The content of boron nitride powder in the inorganic filler may be 20% by mass or more, 40% by mass or more, 100% by mass, 90% by mass or less, 80% by mass or less, 20-100% by mass, 20-90% by mass, or 40-80% by mass, based on the total mass of the inorganic filler.
[0077] The aluminum compound content in the inorganic filler may be 0% by mass, 10% or more by mass, 20% or more by mass, 80% or less by mass, 60% or less by mass, 0-80% by mass, 10-80% by mass, or 20-60% by mass, based on the total mass of the inorganic filler.
[0078] The inorganic filler may contain boron nitride powder and other compounds other than the aluminum compound mentioned above. Examples of other compounds include silicon dioxide, silicon nitride, zinc oxide, and magnesium oxide. The content of other compounds may be 0.1% by mass or more, 1% by mass or less, 0.1 to 1% by mass, or 0% by mass, based on the total mass of the inorganic filler.
[0079] One embodiment of the present disclosure is a resin molded article comprising the boron nitride powder described above and a resin. The resin molded article may further contain at least one aluminum compound selected from the group consisting of aluminum oxide and aluminum nitride. That is, the resin molded article may contain the inorganic filler described above and a resin. The resin molded article may be formed from a resin composition comprising the boron nitride powder described above and a resin, or it may be a cured product of the resin composition. The curing of the resin composition may be, for example, by heat press molding. The resin molded article may be in the form of a sheet, or it may be a heat dissipation sheet.
[0080] The content of boron nitride powder in a resin molded article may be 20% by volume or more, 30% by volume or more, or 40% by volume or more, based on the total volume of the resin molded article, from the viewpoint of further improving the heat dissipation of the resin molded article. The content of boron nitride powder in a resin molded article may be 85% by volume or less, 80% by volume or less, or 70% by volume or less, based on the total volume of the resin molded article, from the viewpoint of suppressing a decrease in insulation and mechanical strength. The content of boron nitride powder in a resin molded article may be adjusted within the above range, for example, 20 to 85% by volume, based on the total volume of the resin molded article.
[0081] The resin may contain a cured resin, or may consist solely of a cured resin. Examples of cured resins that make up the resin include epoxy resins, silicone resins, phenolic resins, melamine resins, urea resins, polyimides, polyamideimides, polyetherimides, and maleimide-modified resins.
[0082] The resin composition described above may contain other components in addition to the boron nitride powder and resin described above. Other components may include, for example, a curing agent. The curing agent may be appropriately selected depending on the type of thermosetting resin. For example, when the resin is an epoxy resin, examples of curing agents include phenol novolac compounds, acid anhydrides, amino compounds, and imidazole compounds. The content of the curing agent may be 0.5 parts by mass or more, or 1 part by mass or more, and may be 20 parts by mass or less, or 15 parts by mass or less, per 100 parts by mass of resin.
[0083] When the resin molded product is in the form of a sheet, the thickness of the resin molded product may be 0.1 mm or more, 1 mm or less, or between 0.1 and 1 mm.
[0084] A method for manufacturing a heat dissipation sheet may include the steps of: molding a mixture containing the above-mentioned boron nitride powder, a curing resin, and a curing agent to obtain a sheet-like molded product; and curing the curing resin by heating while applying pressure in the thickness direction of the molded product to obtain a heat dissipation sheet. The details of the boron nitride powder, curing resin, and curing agent may be the same as those in the above-mentioned resin composition. In the heat dissipation sheet manufacturing method according to this disclosure, since the above-mentioned boron nitride powder is used, the collapse of aggregated particles is suppressed even when kneading with the resin or molding the resin composition, and the pores that occur after molding are small, so a heat dissipation sheet with excellent thermal conductivity and insulation properties can be provided. The molding pressure is 150 kgf / cm². 2 The above is sufficient, and 300 kgf / cm² 2 The following may apply: 150-300 kgf / cm² 2 That's fine.
[0085] Although several embodiments have been described above, this disclosure is not limited in any way to the embodiments described above. Furthermore, the descriptions of the embodiments described above are applicable to each other. [Examples]
[0086] The present disclosure will be described in more detail below with reference to examples and comparative examples. However, the present disclosure is not limited to the following examples.
[0087] (Example 1) [Preparation of boron carbide powder] 100 parts by mass of orthoboric acid (manufactured by Nippon Denko Co., Ltd., hereinafter simply referred to as "boric acid") and 35 parts by mass of acetylene black (product name: HS100, manufactured by Denka Co., Ltd.) were mixed using a Henschel mixer and then packed into a graphite crucible. This graphite crucible was placed in an arc furnace and heated at 2200°C for 5 hours in an argon atmosphere to synthesize a lump of boron carbide (B4C) powder. The synthesized lump of boron carbide powder was pulverized in a ball mill for 1 hour, and then sieved using a sieve to remove coarse particles, thereby producing boron carbide powder (B4C powder) with an average particle size of 20 μm.
[0088] [Preparation of boron carbonitride powder] The prepared boron carbide powder was packed into a boron nitride crucible. The crucible was placed in a resistance heating furnace and heated at 2100°C for 25 hours under a nitrogen gas atmosphere of 0.85 MPa to obtain a calcined product containing boron carbonitride (B4CN4) powder (nitriding process). The calcined product obtained as described above was heated at 800°C for 5 hours under an air atmosphere to obtain a heat-treated product containing boron carbonitride powder (calcination process).
[0089] [Preparation of boron nitride powder] Based on the total amount of the above heat-treated material and boric acid (boron source), boric acid was added so that the content of boric acid, the boron source, was 5% by mass, and the mixture was mixed using a Henschel mixer to obtain a mixture. Next, 2.00 kg of the above mixture was filled into a boron nitride container A, while being appropriately compressed and molded. Next, container A and a boron nitride container B, which was filled with 1.80 kg of boric acid (the boron source), were placed in a resistance heating furnace and heated in a nitrogen gas atmosphere at a pressure of 10 kPa, from room temperature to 2000°C, and held at 2000°C for 5 hours (decarburization process). During the decarburization process, the boric acid in container B volatilized, generating B2O3 gas which was supplied to the mixture in container A. This process decarburized the boron nitride particles and crystallized the individual boron nitride particles within the agglomerated boron nitride particles into hexagonal boron nitride primary particles, thereby synthesizing boron nitride powder containing aggregated particles formed from multiple such primary particles. The synthesized boron nitride powder was crushed in a mortar for 10 minutes and then classified using a nylon sieve with a mesh size of 75 μm. For reference, Figure 1 shows a scanning electron microscope image of the powder. As can be seen from Figure 1, it was confirmed that the growth of primary boron nitride particles was suppressed on the surface of the aggregated particles in the boron nitride powder.
[0090] (Example 2) Boron nitride powder was prepared in the same manner as in Example 1, except that the boric acid content in container A was set to 8% by mass during the decarburization process.
[0091] (Example 3) Boron nitride powder was prepared in the same manner as in Example 1, except that the boric acid content in container A was set to 0% by mass and the boric acid content in container B was set to 3.00 kg during the decarburization process.
[0092] (Example 4) Boron nitride powder was prepared in the same manner as in Example 1, except that the raw material, boron carbide powder, had an average particle size of 25 μm.
[0093] (Example 5) Boron nitride powder was prepared in the same manner as in Example 1, except that the boric acid content in container A was set to 15% by mass during the decarburization process.
[0094] (Comparative Example 1) Boron nitride powder was prepared in the same manner as in Example 1, except that the boric acid content in container A was set to 45% by mass during the decarburization process. For reference, Figure 2 shows a scanning electron microscope image of the appearance of the powder.
[0095] (Comparative Example 2) Boron nitride powder was prepared in the same manner as in Example 1, except that the raw material boron carbide powder had an average particle size of 25 μm and the boric acid content in container A during the decarburization process was set to 45% by mass.
[0096] (Comparative Example 3) Boron nitride powder was prepared in the same manner as in Example 1, except that in the decarburization process, the boric acid content in container A was set to 40% by mass, and container B filled with boric acid was not prepared, with only container A left standing in the furnace.
[0097] <Evaluation of the properties of boron nitride powder> [Orientation Index] First, the X-ray diffraction spectrum of boron nitride powder was obtained by performing X-ray diffraction measurements on the boron nitride powder. From this X-ray diffraction spectrum, the peak intensities I(002) and I(100) corresponding to the (002) and (100) planes were obtained, and the orientation index [I(002) / I(100)] of the boron nitride powder was calculated. The results are shown in Table 1. The X-ray diffractometer used was "ULTIMA-IV" (product name) manufactured by Rigaku Corporation.
[0098] [Pore distribution measurement] Four grams of the boron nitride powder obtained above were compressed and molded under conditions of a diameter of 30 mm and a pressure of 20 MPa to produce a compressed molded body. Next, the pore distribution of the compressed molded body was measured, and a pore distribution curve was obtained. From the obtained pore distribution curve, the ratio of the integrated pore volume Y to the integrated pore volume X, the position of the highest peak in pore volume, and the value of the integrated pore volume X were calculated. The results are shown in Table 1.
[0099] [Average particle size] The particle size distribution of boron nitride powder was measured in accordance with the method described in JIS Z 8825:2013 "Particle size analysis - Laser diffraction and scattering method". A laser diffraction and scattering particle size distribution analyzer (Microtrac "MT-3300EXII" (product name) manufactured by Microtrac-Bell) was used for the measurement. The D50 value in the obtained particle size distribution was taken as the average particle size of the boron nitride powder. The results are shown in Table 1.
[0100] [Bulk density] The bulk density was determined in accordance with the method described in JIS R 1628:1997 "Method for Measuring the Bulk Density of Fine Ceramic Powders". The results are shown in Table 1.
[0101] [Preparation of evaluation sheet] A resin composition was obtained by mixing 100 parts by mass of naphthalene-type epoxy resin (product name: HP4032, manufactured by DIC Corporation) with 10 parts by mass of an imidazole compound (product name: 2E4MZ-CN, manufactured by Shikoku Chemicals Holdings Co., Ltd.) as a curing agent, and then adding boron nitride powder to a mixture containing 50% by volume. A mixing machine manufactured by Shinki Co., Ltd. was used for kneading the resin. The kneading conditions were 1600 rpm for 3 minutes. The obtained resin composition was applied to a PET film to a thickness of 0.3 mm. Afterward, it was subjected to a temperature of 150°C and a load of 200 kgf / cm². 2 A 0.3 mm thick resin sheet (evaluation sheet) was prepared by heating and pressurizing under the specified conditions.
[0102] [Measurement of thermal conductivity] The thermal conductivity was measured using the evaluation sheet described above. Thermal conductivity H (unit: W / (m·K)) is defined as thermal diffusivity A (unit: m 2 ( / second), density B (unit: kg / m³) 3 The thermal diffusivity A was calculated from the values of the thermal density A and specific heat capacity C (unit: J / (kg·K)) based on the formula H = A × B × C. The thermal diffusivity A was determined by the laser flash method using an evaluation sheet processed to a length: 10 mm, width: 10 mm, and thickness: 0.3 mm. The measurement device used was a xenon flash analyzer (product name: LFA447NanoFlash, manufactured by NETZSCH). The density B was determined using the Archimedes method. The specific heat capacity C was determined using a DSC (product name: ThermoPlusEvoDSC8230, manufactured by Rigaku Corporation). The results are shown in Table 1.
[0103] [Measurement of dielectric breakdown voltage] The dielectric breakdown voltage was measured for the evaluation sheets described above. The dielectric breakdown voltage of the obtained evaluation sheets was measured using a withstand voltage tester (device name: TOS-8650, manufactured by Kikusui Electronics Co., Ltd.) in accordance with the description in JIS C 6481-1996 "Test Method for Copper-Clad Laminates for Printed Wiring Boards". The results are shown in Table 1.
[0104] [Viscosity measurement of resin compositions] A resin composition was obtained by mixing silicone oil (product name: KF96L, manufactured by Shin-Etsu Chemical Co., Ltd.) with boron nitride powder to a concentration of 20% by volume. A mixing machine manufactured by Thinky Co., Ltd. was used for kneading the resin. The kneading conditions were 2000 rpm for 3 minutes. The viscosity of the obtained resin composition was measured using a rheometer (product name: MCR302, manufactured by Anton Paar Japan, parallel plate (diameter: 25 mmφ), gap: 1 mm) at 25°C, measuring the viscosity of the slurry from 0.01 to 100 sec. -1 Measured within the range of 4 seconds. -1The results are shown in Table 1. Note that if the viscosity of the resin composition containing boron nitride powder is high, it tends to be difficult to increase the amount of powder that can be filled into the molded body in order to reduce the amount of boron nitride powder used, thereby suppressing the poor handling and moldability of the resin composition. Therefore, a lower viscosity (shear viscosity) obtained by this evaluation is desirable.
[0105] [Table 1]
Claims
1. Boron nitride powder, The boron nitride powder includes aggregated particles composed of aggregated primary particles of hexagonal boron nitride, The crushing strength of the aggregated particles is 10 MPa or more. The orientation index of the boron nitride powder is 10 or less. A molded body made of the boron nitride powder is prepared by compressing the boron nitride powder at a pressure of 20 MPa, and in the pore distribution curve of the molded body obtained by measurement using the mercury intrusion method, When the cumulative pore volume in the range of pore diameters from 0.001 to 300 μm is denoted as the cumulative pore volume X, and the cumulative pore volume in the range of pore diameters from 1 to 300 μm is denoted as the cumulative pore volume Y, the ratio of the cumulative pore volume Y to the cumulative pore volume X is 30% or less. Boron nitride powder in which the highest peak of pore volume is located in the range of pore diameter 1 μm or less.
2. The boron nitride powder according to claim 1, wherein the cumulative pore volume X is 0.5 mL / g or less.
3. The boron nitride powder according to claim 1, wherein the average particle size is 10 to 100 μm.
4. Bulk density is 0.7 g / cm³ 3 The boron nitride powder according to claim 1 is as described above.
5. Boron nitride powder according to any one of claims 1 to 4, An inorganic filler comprising at least one aluminum compound selected from the group consisting of aluminum oxide and aluminum nitride.
6. The method comprises a nitriding step of obtaining boron carbonitride powder by calcining boron carbide powder under a nitrogen-pressurized atmosphere, a calcination step of calcining the boron carbonitride powder under an atmosphere, and a decarburization step of obtaining boron nitride powder by calcining the boron carbonitride powder obtained through the calcination step under a nitrogen-containing atmosphere. A method for producing boron nitride powder, wherein in the decarburization step, diboron trioxide gas is supplied to the boron carbonitride powder.
Citation Information
Patent Citations
Highly thermally conductive sheet
JP2000154265A